Quantitative analysis of phenolic compounds in crude extracts of Myrcia splendens leaves by HPLC-ESI-MS/MS - Paganelli,Camila Jeriane (2020)
Abstract Myrcia splendens is popularly known as “guamirim-de-folha-miúda”, and its occurrence ranges from Mexico to southern Brazil. The aim of this work was to identify and quantify phenolic compounds in the crude hydroalcoholic (EBH), ethyl acetate (EBAE) and dichloromethane (EBDM) extracts using the HPLC-ESI- MS/MS. In total, 15 compounds, including protocatecuic acid, syringic acid, p-coumaric acid, salicylic acid, isoquercetin, ellagic acid, ferulic acid, umbelliferone, coniferaldehyde, sinapaldehyde, carnosol, gallic acid, syringaldehyde, umbelliferone, coniferaldehyde, myricetin and kaempferol were identified. Ellagic acid was the major compound in all extracts.